The role of bacteria and mycorrhiza in plant sulfur supply - Gahan, Jacinta; Schmalenberger, Achim (Frontiers in Plant Science, 2014)
Plant growth is highly dependent on bacteria, saprophytic and mycorrhizal fungi which facilitate the cycling and mobilization of nutrients. Over 95% of the sulfur (S) in soil is present in an organic form. Sulfate-esters and sulfonates, the major forms of organo-S in soils, arise through deposition of biological material and are transformed through subsequent humification. Fungi and bacteria release S from sulfate-esters using sulfatases, however, release of S from sulfonates is catalyzed by a bacterial multi-component mono-oxygenase system. The asfA gene is used as a key marker in this desulfonation process to study sulfonatase activity in soil bacteria identified as Variovorax, Polaromonas, Acidovorax and Rhodococcus. The rhizosphere is regarded as a hot spot for microbial activity and recent studies indicate that this is also the case for the mycorrhizosphere where bacteria may attach to the fungal hyphae capable of mobilizing organo-S. While current evidence is not showing sulfatase and sulfonatase activity in arbuscular mycorrhiza, their effect on the expression of plant host sulfate transporters is documented. A revision of the role of bacteria, fungi and the interactions between soil bacteria and mycorrhiza in plant S supply was conducted.